Development and testing of low-cost animal drawn minimum tillage implements: Experience on Vertisols in Ethiopia - Astatke, A.; Jabbar, M.A.; Mohamed Saleem, M.A.; Erkossa, Teklu (2002)
In Ethiopia, Vertisols which are affected by water logging during the rainy season due to its physical and chemical characteristics are potential agricultural lands but are prone to soil erosion. The soil erosion rates of the cultivated Vertisols are accelerated due to the traditional practices of planting crops at the tail end of the rainy season exposing the bare land to soil detachment. An animal drawn implement, the Broadbed Makers (BBMs), which facilitates the drainage of the Vertisols is used for attaching other implements for minimum tillage practices. Implements have been designed, prototypes produced and tested both on-station. Labour savings, lowering soil erosion rates, reducing rates of seed and fertilizer use and maintaining productivity were achieved by using minimum tillage package.